AKSI KOLEKTIF DALAM GERAKAN PENOLAKAN AHLI FUNGSI LAHAN HUTAN OLEH PERUM PERHUTANI DI DESA SOLOKURO KABUPATEN LAMONGAN - Syifa'ul Qulub; Aribowo Aribowo (Jurnal Politik indonesia (Indonesian Journal of Politics), 2020)
This study focuses on the motives of community participation in collective action in the form of displacement over the function of forest land in Solokuro Village, Lamongan Regency. The researcher used a qualitative descriptive method with the aim to explore the findings. For the theoretical framework, the researcher chose Mancur Olson's collective action theory in exploring the phenomenon of collective movement. This theory explains the motives of individual participation in collection activities, supported by individual’s interests. For communities who have lost their lands, they surely will be involved the collective actions with the hope that they will obtain the land permit back. For society in general, their participation in the movement was aimed to fight for the access of village road. The participation of community leaders and NGOs had purpose to obtain social incentives. Collective action conducted by the people of Solokuro Village succeeded in driving the developer out of the village forest land as a form of collective purposes and it can be seen when the community obtained the forest management permit back, namely Social Forestry Decree.